2013
DOI: 10.1097/sla.0b013e31825ffc37
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Blood Transfusion in Patients Undergoing Major Noncardiac Surgery

Abstract: There was dramatic hospital variability in perioperative transfusion rates among patients undergoing major noncardiac surgery at academic medical centers. In light of the potential complications of transfusion therapy, reducing this variability in hospital transfusion practices may result in improved surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 37 publications
0
70
0
2
Order By: Relevance
“…26 Similarly, Qian et al demonstrated dramatic variation in RBC, fresh frozen plasma, and platelet transfusion utilization between 77 academic hospitals following approximately 80,000 cases of total hip replacement, colectomy, or pancreaticoduodenectomy performed between 2006 and 2010. 27 Aside from the study by Qian et al, the current study is one of the first to investigate the variation in blood transfusion usage for surgical procedures outside of cardiac and orthopedic surgery. Furthermore, it is one of the first studies to analyze both surgeon and hospital-level variation.…”
Section: Discussionmentioning
confidence: 97%
“…26 Similarly, Qian et al demonstrated dramatic variation in RBC, fresh frozen plasma, and platelet transfusion utilization between 77 academic hospitals following approximately 80,000 cases of total hip replacement, colectomy, or pancreaticoduodenectomy performed between 2006 and 2010. 27 Aside from the study by Qian et al, the current study is one of the first to investigate the variation in blood transfusion usage for surgical procedures outside of cardiac and orthopedic surgery. Furthermore, it is one of the first studies to analyze both surgeon and hospital-level variation.…”
Section: Discussionmentioning
confidence: 97%
“…1), and studies over 20 years indicate that a substantial amount of blood is being transfused inappropriately in these patients [3,4]. Variation has also been observed in transfusion rates among patients undergoing major non-cardiac surgery [5], as well as in transfusions among developed countries worldwide (Fig. 2).…”
Section: Auditmentioning
confidence: 96%
“…We need to replace the 'Traditional Concept' that blood products are an effective therapeutic intervention with the 'New Concept' that transfusion of blood products is rather an undesirable outcome. We have learned that transfusion rates are not patientdependent, but are institution (geography) dependent and while 30% of the variation may be surgeon dependent, 70% is hospital specific and that there are 'high-transfusion' hospitals and 'low transfusion' hospitals [74,75] -so we need to change the 'culture' in hospitals, although this is often not easy.…”
Section: Resultsmentioning
confidence: 99%